Light and Electron Microscopic Study of Lungs in Bidri Goat and Deccani Sheep - Ashwani; Pawar, Ashok; Satisha, KB; Girish, MH (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The histological study of lungs in Bidri goat (Capra hircus) and Deccani sheep (Ovis aries) was carried out to know the structural differences in lungs of these animals. Lungs of both the species had respiratory bronchioles, alveolar duct, alveolar sac and alveoli. Respiratory bronchioles were lined by simple cuboidal epithelium in both the species and more number of respiratory bronchioles was seen in adult Bidri goat than adult Deccani sheep. The alveolar ducts were lined by low cuboidal to simple squamous epithelial cells. Alveoli were spherical structures lined by flat and membranous Type-I pneumocytes and large dome shaped Type-II pneumocytes. In transmission electron microscopy (TEM), more numbers of lamellar bodies were seen in cytoplasm of Type-II pneumocytes of Deccani sheep as compared to Bidri goat. Macrophages and mast cells were noticed in interalveolar septa of both the species. In scanning electron microscopy (SEM), no major structural difference was noticed.